Regeneration of testis tissue after ectopic implantation of porcine testis cell aggregates in mice: improved consistency of outcomes and in situ monitoring - Awang Junaidi, Awang Hazmi; Singh, Jaswant; Honaramooz, Ali (CSIRO Publishing, 2020)
Ectopic implantation of donor testis cell aggregates in recipient mice results in de novo formation or regeneration of testis tissue and, as such, provides a unique in vivo model for the study of testis development. However, currently the results are inconsistent and the efficiency of the model remains low. This study was designed to: (1) examine several factors that can potentially improve the consistency and efficiency of this model and (2) explore the use of ultrasound biomicroscopy (UBM) for the non-invasive in vivo evaluation of implants. Testis cell aggregates, containing ~40% gonocytes, from 1-week-old donor piglets were implanted under the back skin of immunodeficient mice through skin incisions using gel matrices or through subcutaneous injection without using gel matrices. The addition of gel matrices led to inconsistent tissue development; gelatin had the greatest development, followed by collagen, whereas agarose resulted in poor development. The results also depended on the implanted cell numbers since implants with 100 × 106 cells were larger than those with 50 × 106 cells. The injection approach for cell implantation was less invasive and resulted in more consistent and efficient testis tissue development. UBM provided promising results as a means of non-invasive monitoring of implants.